Eugenol Potential in Cloves as an Analgesic: Literature Review - Baiq Adinda Aurelia Salsabila; Amira Fathin Nabila Yusuf; Adinda Citra Renda Gading; Anandito Prabuningrat; Mahacita Andanalusia (Jurnal Biologi Tropis, 2023)
Clove (Cloves) is a species of the genus Syzygium, family Myrtacea with the Latin name Syzygium Aromaticum L. or Eugenia Caryophyllata, which is usually used as a spice in cooking and traditional medicine. Because it contains many secondary metabolites, cloves are also used as herbal medicine, namely as a drug to relieve toothache and muscle pain, as well as treat digestive disorders, inhibit blood clotting and lower blood sugar. The review group conducted a study search from several online data centers, namely: Pubmed and Google scholar to obtain studies on the potential of eugenol in cloves as an analgesic. Studies that meet the criteria for writing this article are: (1) studies on the pharmacological potency of eugenol; (2) study research design is a type of original research and experimental; (3) the research subjects in the studies used were in vitro and/or in vivo; (4) The outcome reviewed is the role of eugenol as an analgesic. The author also excludes studies that have one or more predetermined criteria, namely: (1) studies conducted and/or published before 2012; (2) studies on humans as research subjects; (3) the full text of the study is not available. Based on the search method above, five articles were selected.